Determination of UV-Vis Spectrophotometric Method of Metal Complexes Stoichiometry between Cu(II), Ca(II), Cd(II), Mg(II) and Zn(II) with Bupropion Hydrochloride - (:unkn) unknown (INT JOURNAL PHARMACEUTICAL RESEARCH & ALLIED SCIENCES, 2019)
In this study, simple, rapid and accurate UV-Vis spectrophotometric method was developed for the determination of complexes stoichiometry of Cu(II)-bupropion hydrochloride, Ca(II)-bupropion hydrochloride, Cd(II)-bupropion hydrochloride, Mg(II)-bupropion hydrochloride and Zn(II)-bupropion hydrochloride. The spectrums of the complexes formed between bupropion hydrochloride with Cu (II), Ca (II), Cd (II), Mg (II) and Zn (II) metal cations were taken in the range of 500 to 190 nm and the stoichiometry of the complexes formed between bupropion hydrochloride with Cu (II), Ca (II), Cd (II), Mg (II) and Zn (II) metal cations were determined by using the mole ratio method at maximum wavelength (lambda max=252 nm). The stoichiometry of Cu(II)-bupropion hydrochloride, Ca(II)-bupropion hydrochloride, Cd(II)-bupropion hydrochloride and Zn(II)-bupropion hydrochloride were calculated as 1:1, but Mg(II)-bupropion hydrochloride complex was calculated as 1:2. The recovery was found 95.0% for bupropion hydrochloride. Lambert-Beer's obeyed the concentration range of 1.40-6.91 mu g/mL for bupropion hydrochloride. The LOD and LOQ were found to be 13.81 and 1.38 mu g/mL for bupropion hydrochloride, respectively. The interaction between bupropion hydrochloride with Cu (II), Ca (II), Cd (II), Mg (II) and Zn (II) were investigated by applying UV-visible spectrophotometric method, and satisfactory results were obtained.
Keywords: Bupropion Hydrochloride; Metal complex; Mole ratio method; Stoichiometry